Pumping up the volume: vacuole biogenesis in Arabidopsis thaliana - Krüger, Falco; Schumacher, Karin (Seminars in cell & developmental biology, 2018)
Plant architecture follows the need to collect CO2, solar energy, water and mineral nutrients via large surface areas. It is by the presence of a central vacuole that fills much of the cell volume that plants manage to grow at low metabolic cost. In addition vacuoles buffer the fluctuating supply of essential nutrients and help to detoxify the cytosol when plants are challenged by harmful molecules. Despite their large size and multiple important functions, our knowledge of vacuole biogenesis and the machinery underlying their amazing dynamics is still fragmentary. In this review, we try to reconcile past and present models for vacuole biogenesis with the current knowledge of multiple parallel vacuolar trafficking pathways and the molecular machineries driving membrane fusion and organelle shape.
Available online 8 July 2017
Gesehen am 12.09.2018